Endpoint and epitope-specific antibody responses as correlates of vaccine-mediated protection of mice against ricin toxin. Issue 43 (7th October 2020) - Slyke, Greta Van; Ehrbar, Dylan J.; Doering, Jennifer; Yates, Jennifer L.; Vitetta, Ellen S.; Donini, Oreola; Mantis, Nicholas J.
Abstract: The successful licensure of vaccines for biodefense is contingent upon the availability of well-established correlates of protection (CoP) in at least two animal species that can be applied to humans, without the need to assess efficacy in the clinic. In this report we describe a multivariate model that combines pre-challenge serum antibody endpoint titers (EPT) and values derived from an epitope profiling immune-competition capture (EPICC) assay as a predictor in mice of vaccine-mediated immunity against ricin toxin (RT), a Category B biothreat. EPICC is a modified competition ELISA in which serum samples from vaccinated mice were assessed for their ability to inhibit the capture of soluble, biotinylated (b)-RT by a panel of immobilized monoclonal antibodies (mAbs) directed against four immunodominant toxin-neutralizing regions on the enzymatic A chain (RTA) of RT. In a test cohort of mice (n = 40) vaccinated with suboptimal doses of the RTA subunit vaccine, RiVax®, we identified two mAbs, PB10 and SyH7, which had EPICC inhibition values in pre-challenge serum samples that correlated with survival following a challenge with 5 × LD50 of RT administered by intraperitoneal (IP) injection. Analysis of a larger cohort of mice (n = 645) revealed that a multivariate model combining endpoint titers and EPICC values for PB10 and SyH7 as predictive variables had significantly higher statistical power than any one of the independent variables alone. Establishing the correlates of vaccine-mediated protection in mice represents an important steppingstone in the development of RiVax® as a medical countermeasure under the United States Food and Drug Administration's "Animal Rule."